2014
DOI: 10.1002/eat.22285
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric characteristics of the night eating questionnaire in a middle east population

Abstract: The Arabic NEQ generated a lower internal consistency score as compared to previous translations, but a similar factor structure. A cut score of 26 is similar to that determined significant for screening purposes in the original English version, and the proportion of those scoring above it is also similar to those of several international community samples. More research is needed to characterize night eating syndrome, its symptoms, and clinical impact in the Arabic culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…Several studies defined nocturnal ingestions of food as 'eating at night-after having gone to bed-about half the time'. 15,25,26 However, the frequency of nocturnal ingestions based on this cutoff was low in the current study (n = 6). Because of this, we used a less severe cutoff (Table 1).…”
Section: Night-eating Symptomscontrasting
confidence: 58%
“…Several studies defined nocturnal ingestions of food as 'eating at night-after having gone to bed-about half the time'. 15,25,26 However, the frequency of nocturnal ingestions based on this cutoff was low in the current study (n = 6). Because of this, we used a less severe cutoff (Table 1).…”
Section: Night-eating Symptomscontrasting
confidence: 58%
“…Among North American students, two studies found 2.0% NEQ scores above 25 20,22 . Studies conducted among Egyptian students 23 and Turks 24 found, respectively, 5.8% and 9.6% of participants above this cut-off point. In this study, 15.0% of Brazilian students reached NEQ scores ≥ 25.…”
Section: Resultsmentioning
confidence: 89%
“…In fact, recent articles suggest that the prevalence of NES in college students may be higher than the prevalence in the general population, ranging from 1.24 to 9.5% [20][21][22][23][24] . These surveys were conducted among students of different nationalities, but not among Brazilian students.…”
mentioning
confidence: 99%
“…The negative predictive value was high for cut scores of both 25 (95.2%) and 30 (94.0%). 28 The NEQ has been adapted to other languages including German, 24 Spanish, 29 Hebrew, 30 Arabic, 31 and Turkish. 32 The NEQ is also ideal for assessing symptom changes that may occur over the course of NES treatment.…”
Section: Diagnosis and Assessment Of Nesmentioning
confidence: 99%